3-D Visualization and analysis of the pollution sources in the Lake Ohrid - Mitreski, Kosta; Davchev, Dancho (IEEE, 2003)
Our work is related to the ecological state of Lake Ohrid. Tectonic by origin, Lake Ohrid is situated in the southwestern part of the Republic of Macedonia. The size of the lake is 358 squared kilometres. Its average depth is 15 1 m and the maximum depth is 289m. “Man-made” eutrophication, in the abscnce of control measures, proceeds much faster than the natural phenomenon and it is the major reason for pollution of this lake. A Dynamic Integrated Monitoring System (DIMS) was previously prescnted in another paper. Monitoring system is based on on-line measurements. One of the main objectives of DIMS is to provide a real-time monitoring and efficient protcction of the environment. In this paper, a 3-D based analysis of the data from DIMS is given. The main objective of the paper is to show how the critical pollution sources in the Lake Ohrid can bc presented and analyscd by using visualization me thods. ESRI 3-D software (ARCIINFO, ArcVicw Spatial Analyst & Arc View 3D Analyst) for virtual modclling and visualization was used in our work.
Keywords: Pollution, 3-D visualization